Success Analysis of Open Defecation Free (ODF) Program in Bangeran Kecamatan Village, Dawarblandong Mojokerto District - Munawati, Ninik; Sari, Nia; Laila, Siti Farida Noor (Journal for Research in Public Health, 2020)
The results of the 2013 Riskesdas show that households in Indonesia that do not have BAB facilities make defecating openly, which is 12.9%. The difficulty of removing this habit is also influenced by knowledge / understanding of BABS hazards, problems of poverty (unable to make toilets), landlessness, living in homes that do not have toilets, or in environments that strongly support the practice of BABS, such as riverside, bushes. bush, and lack of awareness, so that the practice of BABS is normal. The purpose of this study was to analyze the factors that influence the success of the Open Defecation Free (ODF) Program in Bangeran Village, Dawarblandong District, Mojokerto Regency. The study design used a quantitative cross sectional. The study sample was 276 families after triggering STBM "Yuk Jum Berseri" which was taken using cluster sampling. Sources of data use primary data obtained by distributing questionnaires and interviews. Data analysis using multiple logistic regression tests. The results showed jointly Knowledge (X1), Attitudes (X2), Availability of family latrines (X3), distance of houses other than latrines (X4) and regulations (X5) related to Open Defecation (OD) (Y) behavior. Partially only the variable distance of the house with the defecation place other than the toilet (X4) which does not affect the behavior of Open Defecation (OD) (Y).